Comparing index-based vulnerability assessments in the Mississippi Delta: Implications of contrasting theories, indicators, and aggregation methodologies. (October 2019) - Anderson, Carl C.; Hagenlocher, Michael; Renaud, Fabrice G.; Sebesvari, Zita; Cutter, Susan L.; Emrich, Christopher T.
Abstract: There are many index-based approaches for assessing vulnerability to socio-natural hazards with differences in underlying theory, indicator selection and aggregation methodology. Spatially explicit output scores depend on these characteristics and contrasting approaches can therefore lead to very different policy implications. These discrepancies call for more critical reflection on index design and utility, a discussion that has not kept pace with the impetus for vulnerability assessments and respective index creation and application following the Hyogo Framework for Action 2005–2015. Comparing index outputs is an effective approach in this regard. Here, the Social Vulnerability Index (SoVI ® ) and the vulnerability component of the Global Delta Risk Index (GDRI) are applied at census tract level in the Mississippi Delta and visually and quantitatively compared. While the SoVI ® is grounded in the hazard/risk research paradigm with primarily socio-economic indicators and an inductive principal component methodology, the GDRI incorporates advancements from sustainability science with ecosystem-based indicators and a modular hierarchical design. Maps, class rank changes, and correlations are used to assess the convergence and divergence of these indexes across the delta. Results show that while very different theoretical frameworks influence scores through indicator selection, methodology of index calculation has an even greater effect on output. Within aggregative methodology, the treatment of inter-indicator correlation is decisive. Implications include the need for an increased focus on index methodology and validation of results, transparency, and critical reflection regarding assessment limitations, as our results imply that contradictory risk reduction policies could be considered depending on the assessment methodology used. Highlights: Aggregation methodology of index-based vulnerability assessments can influence scores more than theory and indicator choice. Improvement of aggregation methodology through validation has not kept pace with index creation. Such assessments must acknowledge limitations in design and confidence in results to avoid misguided policy decisions.